Peculiarities of angiogenesis in testicular embryonal carcinoma - Potapov, S. M.; Halata, D. I.; Pliten, O. M.; Halata, A. I. (Journal of Education, Health and Sport, 2019)
Despite the relatively low incidence of testicular germ cell tumors (TGCT), which amount only 1% of all cancers in men worldwide in the epidemiological aspect, unlike tumors of other localizations, it does not become more frequent with age, but reaches its peak in young men of working age what attaches to the problem not only great medical, but also social significance. Estimation of angiogenesis in the tumor is considered as one of the markers for predicting the course of disease, presence of metastases and sensitivity to antitumor antiangiogenic therapy. At the same time, data concerning the study of the mechanisms of blood vessels formation, the work out of methods for estimation of tumorous angiogenesis as well as the use habits of IHC markers of endothelial cells (CD31 and CD34) for assessing the aggressiveness and prognosis of TGCT and, in particular, EC, are absent in the available literature sources. Investigation of peculiarities of neoangiogenesis in the dynamics of testicular embryonal carcinoma progression revealed: significant increasing of relative area of CD31 and CD34 expression as well as vascular density during transition from the initial to the late stages of tumor progression; formation of intratumoral vessels in the embryonal carcinoma occurs by angiogenesis and vasculogenesis with participation of progenitor endothelial cells; embryonal carcinoma is characterized by vasculogenic mimicry in the form of channels formation that do not have endothelial lining.